2022
DOI: 10.17221/168/2022-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Economic overview of the distribution channels used by Eastern European small farms for their agricultural products

Abstract: The role of small farms in agricultural production is particularly important for less developed economies, with a high share of agriculture in GDP and a lower level of national income. These economies have a high share of small-scale farms in the total number of registered farms, measured by the size of an agricultural holding. The paper thoroughly analyses the distribution channels of the agricultural products of Moldova (MDA), Romania (ROM), and Serbia (SRB). The data sources for this analysis are taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Various models have been developed and used effectively for the decision-making problem considering several factors/criteria [31,32]. Saaty's Analytical Heuristic Process (AHP method) has been widely used for several decades in numerous sec-tors of the economy, mining [33], agroeconomy [34], the IT sector [35], banking [36], sustainable development [26], etc. Rezeai's Best-Worst Method (BWM) is a newer MCDM technique that resolves the inconsistency of pairwise comparisons.…”
Section: General Reviewmentioning
confidence: 99%
“…Various models have been developed and used effectively for the decision-making problem considering several factors/criteria [31,32]. Saaty's Analytical Heuristic Process (AHP method) has been widely used for several decades in numerous sec-tors of the economy, mining [33], agroeconomy [34], the IT sector [35], banking [36], sustainable development [26], etc. Rezeai's Best-Worst Method (BWM) is a newer MCDM technique that resolves the inconsistency of pairwise comparisons.…”
Section: General Reviewmentioning
confidence: 99%
“…Nedeljković et al (2023) use the TOPSIS method of multi-criteria decision-making to select marketing channels for a farming company. Ristanović et al (2022) use the AHP method to analyse sales marketing channels, finding that farmers most often distribute their products through green markets, with price and quality being the dominant factors influencing channel choice. Earlier, using the same methodology, Tošović-Stevanović et al (2020) found that selling through processing capacities is the best option.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid models are being developed, and new methods are emerging. These tools cover almost all areas of the business world, for example, the area of public investment [26], energy efficiency [17], diagnostics in medicine [36], the food industry [6], renewable energy production [4,28], banking services [69], forecasting carbon price [2], location selection [43], distribution channels in the agricultural economy [56,66], the choice of technology in urban wastewater treatment [54], assessing the quality scientific outputs [60], metaheuristic-based optimization algorithms [19], and, more importantly, in the field of risk management [32,37,38], especially in the area of operational risk [55].…”
Section: Introductionmentioning
confidence: 99%